Patient Reported Outcomes Measurements Information System in Stroke Patients in Full and Shortened Format - Lens, Charlotte; Demeestere, Jelle; Vanhaecht, Kris; Lemmens, Robin (Frontiers in Neurology, 2021)
Introduction The modified Rankin Scale (mRS) after 90 days documents outcome in stroke patients, but focusses only on activities of daily living. Here we studied stroke outcome beyond these activities by the Dutch-Flemish version of the Patient Reported Outcomes Measurement Information System (PROMIS) questionnaire. Patients and methods We documented the mRS at day 90 in stroke patients who filled out a questionnaire on pain intensity and seven PROMIS domains: physical function, ability to participate in social roles, anxiety, fatigue, depression, sleep disturbance, pain interference. In a subgroup of patients this questionnaire was reduced to one overall question per PROMIS domain. We correlated these findings with the mRS. Results We received 102 questionnaires and identified physical function as the most affected PROMIS domain. The strongest correlation with mRS was found for the health domains of physical function (ρs = 0.70, p<0.001) and ability to participate in social roles (ρs = 0.61, p<0.001). The other domains with substantial proportions of patients with worse scores compared to the general population (19-44%) correlated weakly with the mRS. We identified a strong correlation between the single question per health domain and the overall score per PROMIS domain. Discussion and conclusion: PROMIS better reflects the overall health status of stroke patients beyond functional outcome as measured by the mRS. Simplification of the questionnaire with a single question per PROMIS domain could potentially replace the full questionnaire, but needs further validation.